First steps towards energy efficient area-keeping stratospheric balloons - Tang, Ryan Haoyang (2019)
Stratospheric balloons with area-keeping capabilities have the potential to disrupt the near-space industry. Being able to act as a pseudo-satellite, this class of balloons will be able to provide low-cost coverage over an area of interest. Some examples include balloons equipped with antennas and other telecommunication equipment to provide network coverage to rural or disaster-stricken areas. In this paper, we studied the recent implementations of area-keeping stratospheric balloons and formulate an algorithm to use atmospheric winds to navigate the balloon in the stratosphere. Using global forecasted wind data, our algorithm was able to obtain the trajectory for a balloon to travel from one point in space to another with minimal energy usage. Varying atmospheric conditions such as temperature, air pressure and density were also considered in our algorithm. The results obtained for a simulated launch from Singapore and Alice Springs, Australia was also evaluated and discussed.